The Effect of DAR, Asset Growth, and DER on ROA in Indonesian CPO Companies with ROE Serving as an Intervening Variable - Khaeril Anwar Junaedi; Muhammad Ali; Mursalim Nohong; Arifuddin Arifuddin (Daengku: Journal of Humanities and Social Sciences Innovation, 2026)
This study aims to evaluate the direct effects of the Debt to Asset Ratio (DAR), Asset Growth (AG), and Debt to Equity Ratio (DER) on the Return on Assets (ROA) of Crude Palm Oil (CPO) companies listed on the Indonesia Stock Exchange in 2025. It also examines the role of Return on Equity (ROE) as an intervening variable in explaining the relationship between capital structure, company growth, and profitability. The research methodology employs path analysis, with the path coefficient values indicated by the coefficients of multiple linear regression. The path coefficients for DAR, AG, DER, and ROE in relation to ROA were found to be 0.376, 0.025, -0.405, and 0.807, respectively, with a p-value of ?0.003. In contrast, the path coefficients from DAR, AG, and DER to ROE were -0.745, 0.128, and 0.574, respectively, with a p-value of ?0.060. When analyzing the influence of ROE on ROA, the Sobel Test results indicated that the p-values for the DAR, AG, and DER variables were 0.000, 0.060, and 0.000, respectively. These results suggest that ROA is significantly influenced directly by DAR, AG, DER, and ROE. Additionally, ROE is significantly affected by DAR, AG, and DER. It was also demonstrated that ROE plays a substantial mediating role in the relationship between ROA.